Graphene Oxide Nanosheets for Bone Tissue Regeneration - Zapata-Ramirez, P (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Bone tissue engineering is a promising alternative to repair wounds caused by cellular or physical accidents that humans face daily. In this sense, the search for new graphene oxide (GO) nanofillers related to their degree of oxidation is born as an alternative bioactive component in forming new scaffolds. In the present study, three different GOs were synthesized with varying degrees of oxidation and studied chemically and tissue-wise. The oxidation degree was determined through infrared (FTIR), X-ray diffraction (XRD), X-ray photoelectron (XPS), and Raman spectroscopy (RS). The morphology of the samples was analyzed using scanning electron microscopy (SEM). The oxygen content was deeply described using the deconvolution of RS and XPS techniques. The latter represents the oxidation degree for each of the samples and the formation of new bonds promoted by the graphitization of the material. In the RS, two characteristic bands were observed according to the degree of oxidation and the degree of graphitization of the material represented in bands D and G with different relative intensities, suggesting that the samples have different crystallite sizes. This size was described using the Tuinstra–Koenig model, ranging between 18.7 and 25.1 nm. Finally, the bone neoformation observed in the cranial defects of critical size indicates that the F1 and F2 samples, besides being compatible and resorbable, acted as a bridge for bone healing through regeneration. This promoted healing by restoring bone and tissue structure without triggering a strong immune response. © 2024 by the authors.